Characteristics and information searched for by French patients with systemic lupus erythematosus: A web-community data-driven online survey. (April 2016) - Meunier, B; Jourde-Chiche, N; Mancini, J; Chekroun, M; Retornaz, F; Chiche, L
Introduction: To provide information about the needs of patients with systemic lupus erythematosus (SLE) using Carenity, the first European online platform for patients with chronic diseases. Methods: At one year after its creation, all posts from the Carenity SLE community were collected and analysed. A focused cross-sectional online survey was performed. Results: The SLE community included 521 people (93% females; mean age: 39.8 years). Among a total of 6702 posts, 2232 were classified according to disease-related topics. The 10 most common topics were 'lupus and …' either 'treatment', 'fatigue', 'entourage', 'sun exposure', 'diagnosis', 'autoimmune diseases', 'pregnancy', 'contraception', 'symptoms' or 'sexuality'. 112 SLE patients participated in the online survey. At the time of diagnosis, only 17 (15%) patients had heard of SLE and 84 (75%) expressed a need for more information on outcomes (27%), treatments (27%), daily life (14%), patients' associations (11%), symptoms (8%), the disease (8%) and psychosocial aspects (7%). When treatment was initiated, 48 patients (43%) would have liked more information about side effects (46%), long-term effects (21%), treatment duration/cessation (12.5%) and type (10%) and mechanism of action (8%) of treatments. All participants except one had used the internet to find information about SLE. Sources of information included healthcare providers (51%/61%/67%), journals/magazines (7%/12%/6%), lupus Websites (51%/77%/40%), web forums/blogs (34%/53%/19%), patients' associations (11%/23%/9%) accessed at 'just before diagnosis', 'just after diagnosis' and 'before treatment initiation'. Conclusions: Online patient communities provide original unbiased information that can help improve provision of information to SLE patients.